(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study explores the transformative impact of digital technologies on the functioning of libraries within engineering institutions in Jammu.With the rapid advancement of information and communication technologies (ICT),libraries have undergone a significant shift from traditional to hybrid and digital models. The research examines how digital tools—such as online databases, e-resources, digital cataloging systems, and library automation software—have enhanced information access, resource sharing, and user services. Using a mixed-methods approach, data were collected through surveys and interviews with librarians, faculty, and students across several engineering colleges in the region.The findings reveal a positive correlation between the adoption of digital technologies and improvements in operational efficiency, user satisfaction, and resource utilization. However, challenges such as limited digital infrastructure, lack of training, and budget constraints continue to hinder full-scale implementation. The paper concludes by recommending strategic investments, policy reforms, and capacity-building initiatives to strengthen the digital capabilities of academic libraries in Jammu’s engineering institutions.